Queer Data - Keilty, Patrick; Cifor, Marika; Watson, B.M.; Weibe, Andrew (Proceedings of the Association for Information Science and Technology, 2024)
ABSTRACT Data is both a worldmaking and a dismantling force. This panel brings together four approaches to queer data studies. The first talk focuses on genealogies of queer data studies, providing its intellectual history and foundations. The second talk examines a historically significant moment of queer data activism during the height of the HIV/ AIDS pandemic. The third talk examines current queer metadata interventions for libraries and archives. Finally, guided by queer approaches to computational data, the fourth talk focuses on forms of identification for Indigenous queer subjects in archives.